Factores asociados al retraso lingüistico del habla en niños de 2 a 3 años del centro de cuidados infantiles en Babahoyo creciendo con nuestros hijos (CNH) - Jerez Barreno, Joselyn Carolina (2025)
The present research is focused on determining the elements that contribute to verbal language contribute to verbal language delay in children aged 2 to 3 years, examining the impact of digital the impact of the use of digital platforms, the role of emotional attachment, and the influence of influence of educational programs. The research, with a mixed approach and non-experimental design, analyzed the degree of language design, analyzed the degree of linguistic development of the children and the contextual and personal contextual and personal factors associated with the delay. The findings point to the importance of the importance of considering the impact of digital platforms on early linguistic early linguistic development, as overexposure to screens can significantly delay language significantly delay language by reducing necessary social interaction necessary. In addition, the study underscores the importance of emotional attachment and a stimulating environment for healthy language development. for healthy language development. Adequate care and emotional support and emotional support from caregivers, as well as physical activities and outdoor play that promote interpersonal that promote interpersonal communication are crucial to avoid language delays.language delays.